Ecosystem Trial Strategic Plan Friendly Trial -ProACT - Doyle, Julie; Caprani, Niamh; Gavin, Shane; Jacobs, An; Kuiper, Janneke; Dinsmore, John; Hoogerwerf, Evert-Jan; Hannigan, Caoimhe (European Commission, 2016)
The purpose of this deliverable is to provide implementation plans for testing and evaluating the ProACT system. To reflect the iterative project implementation cycle, this document will be reviewed and updated twice during the life cycle of the project (M23 and M39). The current version of this deliverable outlines the framework for implementing the friendly trial and for evaluating its results. We define a friendly trial as a trial to test the robustness of a technology ecosystem, prior to deployment to real end users. Participants of the friendly trial will be members of research teams at trial sites. During the friendly trial, participants will ‘act’ as ProACT stakeholders, testing an end-to-end integrated ProACT ecosystem. This deliverable outlines the technology to be deployed in the friendly trial, how data will be managed, the study design, and what we will evaluate. The latter includes technology robustness (for example, data flow between sensors, the ProACT back end architecture and end user interfaces; reliability of technology), system analytics (usage and system performance), and user feedback (usefulness, satisfaction, user burden). Outcomes from the friendly trial will contribute to refinement of the technology ecosystem and the protocol for the main Proof of Concept (PoC) trial. It is important to note that this document describes the formal friendly trial. In reality, as new devices are introduced (e.g. novel sensors) and new applications are designed, developed and iterated upon leading up to the PoC trial, researchers at trial sites will retain a kit and continue to test when any new piece of technology is introduced into the ProACT ecosystem. As described in the grant agreement, this deliverable is designed to be an iterative document, with updates due for submission at M23 and M39. These updates to the deliverable will include additional protocols for conducting the main PoC trial and the transfer feasibility study.
Keywords: ProACT; Assistive technology; Patient-centred care; Ageing; Digital Engagement; Chronic Disease Management; Digital Health; Friendly Trial; multimorbidity; Age-related disability; Chronic Health Condition; Health